The social innovation profile in students as a transformation strategy: structural equation modeling - Glasserman-Morales, Leonardo David; Alcantar-Nieblas, Carolina; Nava-Lara, Sergio (Frontiers in Education, 2024)
The development of social entrepreneurship competencies in university students favors the generation of proposals for solutions to different social problems, thus promoting a positive social impact capable of transforming people's living conditions. This study aims to analyze the relationship between the dimensions of social entrepreneurship competence: entrepreneurial management, social value, leadership, effective communication and social innovation. A total of 408 higher education students from 13 countries and six different disciplinary areas participated in the study, ranging in age from 18 to 58 years (M = 22.4, SD = 6.0). The social entrepreneurship instrument was used, which is composed of 28 items grouped into five dimensions. A structural equation model was calculated. The findings indicate that entrepreneurial management, social value, and leadership are directly and positively related to personal competencies and social innovation. These results prove the importance of social entrepreneurship training in the development of social innovation in students, it is important that educational institutions in general carry out a review of their curricula and programs that take into account the development of social innovation competence as a factor that can enhance social change.